Debussy and his world - Fulcher, Jane F. (Classical music reference library., 2001)
Claude Debussy's Paris was factionalised, politicised, and litigious. This text aims to capture the complexity of the composer's restless personal and artistic identity within the context of fin-de-siècle Paris.